The Sense of Capability Scale Adaptation in Peruvian Students - Herrera, Dora (2023)
Background: The sense of capability scale, originally validated in French university students (Drouin & Costalat-Founeau, 2020), measures people’s subjective representation of their own capacities and theirperceptions of what others think about them. The aim of this study is to adapt the scale for university students in Lima, Peru and to analyze its psychometric properties. Method: 516 students from a private university completed the questionnaire. Factor analysis and correlations were used to determine evidence of validity. Cronbach’s alpha and McDonald’s omega were used to evaluate reliability. Results: Contrary to the original 2-factor structure, our results suggested a single-factor solution that explained 52% of the variance; the items had high loadings. The model was confirmed by a best fit (χ2 = 362.84; df = 35; p < .001; CFI = .99; TLI = .98; SRMR = .06; RMSEA = .10). A moderate positive correlation was found with positive affect and flourishing, as well as a moderate negative correlation with negative affect. There were no significantdifferences by sex, level, and career type. Conclusion: The new version of the scale shows evidence of adequate validity and reliability (α = .88) in students of a private university in Lima, Peru.